2007
DOI: 10.1111/j.1532-5415.2007.01397.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity Profile of the Concomitant Administration of ZOSTAVAX and Inactivated Influenza Vaccine in Adults Aged 50 and Older

Abstract: ZOSTAVAX and influenza vaccine given concomitantly are generally well tolerated in adults aged 50 and older. Ab responses were similar whether ZOSTAVAX and influenza vaccine were given concomitantly or sequentially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 12 publications
2
51
0
2
Order By: Relevance
“…This was tested in an RCT in which 762 adults ≥ 50 years received a single dose of live HZ vaccine, either concomitantly (n = 382) or not (n = 380), with an inactivated split influenza vaccine [48]. The virus-specific immune responses 4 weeks after vaccination were comparable for both vaccines, regardless of whether the vaccines were administered concomitantly or not.…”
Section: Coadministration With Other Vaccinesmentioning
confidence: 99%
“…This was tested in an RCT in which 762 adults ≥ 50 years received a single dose of live HZ vaccine, either concomitantly (n = 382) or not (n = 380), with an inactivated split influenza vaccine [48]. The virus-specific immune responses 4 weeks after vaccination were comparable for both vaccines, regardless of whether the vaccines were administered concomitantly or not.…”
Section: Coadministration With Other Vaccinesmentioning
confidence: 99%
“…13 In studies evaluating concomitant administration of influenza and pneumococcal vaccines administered at separate sites, no significant reduction in antibody responses or safety concerns were identified. 14,15 There are some reports in the pediatric literature of lower-than-expected differences would have predicted higher responses in the concomitant group than in the non-concomitant group.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the noninferiority of VZV antibody titers, the margin of 1.5-fold was based mainly on the variability of the antibody responses that were observed in previous studies which showed that the standard deviation (SD) of the natural log-transformed VZV antibody titers was about 1.2. 13,21 Given the study sample size, in order for this study to claim noninferiority in terms of VZV antibody response, the minimum observed GMT ratio would have to be <0.25 (in natural log), which is less than onequarter of the variability of VZV antibody in natural log scale.…”
Section: Methodsmentioning
confidence: 99%
“…Concomitant administration of the zoster vaccine with inactivated influenza vaccine does not alter the immunogenicity of either vaccine [93]. Although the FDA initially prohibited concurrent use of the zoster and pneumococcal vaccines after an RCT suggested that this may result in lower VZV antibody levels [94], this guidance has now been revised.…”
Section: Development Of a Vaccine Against Zoster Efficacy And Safetymentioning
confidence: 99%